2020
DOI: 10.3390/jcm9061814
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Fibromyalgia Indicates an Autoimmune Origin of the Disease and Opens New Avenues for Targeted Therapy

Abstract: Fibromyalgia is a chronic disorder characterized by widespread pain and by several non-pain symptoms. Autoimmunity, small fiber neuropathy and neuroinflammation have been suggested to be involved in the pathogenesis of the disease. We have investigated the gene expression profile in peripheral blood mononuclear cells obtained from ten patients and ten healthy subjects. Of the 545,500 transcripts analyzed, 1673 resulted modulated in fibromyalgic patients. The majority of these genes are involved in biological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
(42 reference statements)
1
26
0
1
Order By: Relevance
“…IL-6 is involved in the onset and persistence of pain, and elevated levels have been found in patients with chronic pathological pain [ 118 , 119 ]. Many studies have described increased serum/plasma IL-6 levels in FM patients [ 5 , 91 , 96 , 97 , 98 , 99 ], and these have even been correlated with the intensity of pain [ 100 ]. Elevated levels of this biomolecule have also been observed in skin biopsies from FM patients [ 95 ] and in their peripheral blood mononuclear cells [ 92 ], which was found to be related to hyperalgesia, fatigue, and depression.…”
Section: Potential Salivary Biomarkers In Fmmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is involved in the onset and persistence of pain, and elevated levels have been found in patients with chronic pathological pain [ 118 , 119 ]. Many studies have described increased serum/plasma IL-6 levels in FM patients [ 5 , 91 , 96 , 97 , 98 , 99 ], and these have even been correlated with the intensity of pain [ 100 ]. Elevated levels of this biomolecule have also been observed in skin biopsies from FM patients [ 95 ] and in their peripheral blood mononuclear cells [ 92 ], which was found to be related to hyperalgesia, fatigue, and depression.…”
Section: Potential Salivary Biomarkers In Fmmentioning
confidence: 99%
“…This pro-inflammatory cytokine is produced by Th-17 cells and participates in inflammatory processes, promoting the production of chemokines and granulocyte colony-stimulating factors and mobilizing immune cells to infection sites [ 112 , 124 ]. Elevated serum levels of this cytokine have been widely reported in FM patients [ 99 , 106 ], and some authors have related its presence to characteristic symptoms of the disease, such as anxiety [ 125 ] and pain [ 126 ].…”
Section: Potential Salivary Biomarkers In Fmmentioning
confidence: 99%
“…It is also noted that high levels of CD4+ T cells produced by circulating IL-17 and of serum cytokines such as TGF-beta, IL-6, IL-21 and IL-23 that promote Th17 differentiation, survival and expansion in fibromyalgic patients, therefore settling the gene expression signature and the presence of a continuing inflammation. This study also found two uncharacterized LncRNAs that aim, and regulate networks of genes that are included in numerous characteristics of fibromyalgia through their miRNA [5]. Diagnosis of fibromyalgia is not that easy because the disease is described as multifactorial, and very little information is known about the causes of the disease.…”
Section: Introductionmentioning
confidence: 71%
“…Immunologic alterations are added to genetic, hormonal, environmental, and neural factors and can contribute to the development of an inflammatory state ( 151 ). Interestingly, a very recent genetic study investigated the gene expression profile in patients with FM, finding that most of modulated genes belonged to the IL-17 pathway and to the type I IFN signatures, suggesting an autoimmune component for this disease ( 152 ). These data corroborate the findings of increased serum levels of pro-inflammatory cytokines, such as IL-1, IL-6 and IL-17, found in patients with FM ( 153 ).…”
Section: Psoriatic Arthritis Comorbiditiesmentioning
confidence: 99%